Primary school-based screening for childhood mental health problems and intervention delivery: a qualitative study of parents in challenging circumstances. Issue 4 (2nd October 2022) - Williamson, Victoria; Larkin, Michael; Reardon, Tessa; Ford, Tamsin; Spence, Susan H.; Morgan, Fran; Creswell, Cathy
ABSTRACT: Few children with mental health problems access evidence-based interventions. Primary schools may be an ideal setting to improve access to treatment through screening and intervention programmes, but some families' circumstances and experiences may increase barriers to benefiting from this approach. Interviews were carried out with parents of children living in potentially challenging circumstances, including foster and military-connected families. We aimed to explore parent perceptions of a school-based screening/intervention programme and potential barriers to uptake. Parents described that due to their past experiences, that they might not trust or engage with a school-based screening/intervention. Nonetheless, parents considered that the delivery of a sensitive school screening/intervention programme might provide an opportunity for schools to strengthen their relationship with families. These findings highlight the need for future school-based screening/intervention programmes for child mental health to consider the needs of families of children from varied circumstances, and ensure steps are taken to promote trust.